MENINGKATKAN PEMAHAMAN GURU TERHADAP BAHASA ANAK SEBAGAI UPAYA HARMONISASI KOMUNIKASI DALAM PEMBELAJARAN - Deni Wardana; Utami, Putri Arianita (Dharma: Jurnal Pengabdian Masyarakat, 2025)
Schools must support increasing teacher understanding in communication, especially communication with students. This research relates to teacher communication in understanding children's language at the Sekolah Dasar Laboratorium Percontohan (SDLP) in Serang. Sekolah Dasar Laboratorium Percontohan has eight teachers, including one principal. This community service activity in the form of a scientific discussion has the aim of knowing the initial understanding of the SDLP UPI Campus teachers in Serang regarding children's language, knowing the teacher's understanding after this activity, and the teachers' responses to the content of this community service activity. This phenomenon is supported by the Primary School Teacher Education Study Program (PGSD) at the Indonesian Education University (UPI) Campus in Serang because it is very suitable for the study program's annual program. This service activity received a positive response from the teachers as the target of the activity, the teachers already had sufficient abilities to teach in elementary schools, and there was an increase after this service was carried out for teachers at the SDLP UPI Campus in Serang.